Determinants of caesarean section among women of childbearing age in Indonesia: Secondary data analysis of the 2017 Indonesia Demographic Health Survey - Desak Nyoman Purniati; Dewa Nyoman Wirawan; Luh Seri Ani (Universitas Udayana, 2020)
Background and purpose: The caesarean section (CS) trendcontinues to increase throughout the world, including Indonesia. Indonesia is one of the countries where the proportion of CS exceeds the WHO recommendation. CS on medical indications can save the mother and baby, but if the CS is performed without any medical indication it will affect the welfare and health of both. This study was conducted to determine the factors associated with CS deliveries in women of childbearing age (WCA) in Indonesia. Methods: This study is a secondary data analysis using the 2017Indonesia Demographic and Health Survey (IDHS) data. The data analyzed in this study were CS deliveries in the last 5 years and predictors variables which were collected via interviews. The number of samples in this analysis were 14,533 respondents from the total sample size of the 2017 IDHS as many as 50,730 female respondents aged 15-49 years. Data analysis was performed using multivariate logistic regression with backward method. Results:The proportion of CS among women aged 15-49 years in Indonesia was 17.7% (95%CI: 17.4-18%). The risk factors for CS were age >35 years with AOR=2.35 (95%CI: 1.61-3.44), primiparity with AOR=2.03 (95%CI: 1.54-2.68), multiparity with AOR=1.53 (95%CI:1.18-1.99), low infant weight with AOR=1.71 (95%CI: 1.45-2.03),maternal high education level with AOR=2.15 (95%CI: 1.79-2.59), husband’s middle education level with AOR=1.41 (95%CI: 1.231.62), urban areas of residence with AOR=1.28 (95%CI: 1.15-1.41), high family wealth index with AOR=1.87 (95%CI: 1.64 2.13), hasa health insurance with AOR=1.54 (95%CI: 1.41–1.70), delivered the baby at a private health facility with AOR=1.18 (95%CI: 1.07-1.31), number of ANC visits ≥4 times with AOR=1.87 (95%CI: 1.42-\2.32), and have been exposed to information media with AOR=2.01(95%CI: 1.02-3.97). Conclusion: The proportion of CS delivery in Indonesia remains relatively high. Education for mothers and families about the impact of unnecessary CS delivery needs to be increased so that mothers and families are able to make appropriate and rational decisions. Interventions should be focused on mothers and husbands who are more educated, have higher socioeconomic status, live in urban areas and have chosen delivery in private health facilities